A new ent-kaurane diterpene derivative from the stems of Eurya chinensis R.Br. Issue 2 (17th January 2018) - Song, Jia-Ling; Yuan, Yao; Nie, Ling-Hui; Li, Bai-Lin; Qin, Xu-Bing; Li, Yan; Wu, Jie-Wei; Qiu, Sheng-Xiang
Abstract: One new ent -kaurane diterpene derivative (1 ), along with four known diterpenes, was isolated from the stems of Eurya chinensis R.Br. The structure of the new compound was established by extensive analysis of mass spectrometric and 1D and 2D NMR spectroscopic data. Compound1 showed moderate anti-inflammatory activities with IC50 value of 8.12 μM. This is the first example of diterpenoids with 4-hydroxy-4-(2-hydroxyethyl)-1-hydroxyl-cyclohexanoyl substituent. Abstract :